Polymorphism of Fat Mass and Obesity Associated (FTO) gene as a risk Factor for Type 2 Diabetes Mellitus with Metabolic Syndrome at DR Sardjito Hospital Yogyakarta - Seto Priyambodo; Ahmad Hamim Sadewa; Maliyah Madiyan (Faculty of Medicine Universitas Mataram, 2012)
Introduction . FTO gen is one of the new recently studied and still requires a lot of studies on the role of this gen on the incidence of metabolic syndrome. FTO rs 9939609 polymorphism in some populations have mentioned as the risk factors for obesity, type 2 diabetes mellitus and metabolic syndrome. Protein FTO role in demethylations of the genes in the hypothalamus that helps maintain energy intake and expenditure. Methods This study used a case- control design with type 2 DM subjects with metabolic syndrome (n = 40) as cases and type 2 diabetes mellitus without metabolic syndrome (n = 40) as a control from DR.Sardjito Hospital Yogyakarta 2009-2010. FTO gen rs9939609 polymorphism was analyzed by PCR-RFLP. Chi square test and odds ratio test are used to examine FTO rs9939609 polymorphism and the relationship with the incidence of type 2 diabetes with metabolic syndrome and it’s components. Results The frequency of TT genotype in subjects with type 2 DM patients with metabolic syndrome 2(5%), AT genotype 35 (87.5%) and AA genotype 3 (7.5%) (n = 40). In subjects with type 2 DM patients without metabolic syndrome TT genotype frequency 6 (15%), AT genotype 32 (80%) and AA genotype 2 (5%) (n = 40).OR are significant for sistolic hypertension (OR=0,039) and for HDL plasma level (OR=0,046) as the components of metabolic syndrome. Conclusion The FTO gen rs9939609 polymorphism is the risk factor for hypertension and high HDL plasma level as the components of metabolic syndrome at DR Sardjito Hospital Yogyakarta.